Speed Reading: Tips for understanding reading in an easy way - Athia Fidian (Universitas Muhammadiyah Magelang, 2024)
Reading is the process by which readers construct meaning by combining information from a text with their prior knowledge. It is a valuable ability that is closely tied to others such as speaking, listening, and writing. Reading is a critical component of language skills since it is the most practical skill in everyday life. In the English context, most readers struggle because they lack and are unfamiliar with efficient tools for understanding the meaning of the text. In addition, many EFL students continue to struggle with reading comprehension due to ineffective reading practices. As a result, this article offers suggestions for simple approaches to comprehend reading material.